Review of Copyright Regulations for Songs Created by Artificial Intelligence in Indonesia (West Science Interdisciplinary Studies, 2025)
This study aims to analyze the copyright regulation of works created by Artificial Intelligence (AI) in Indonesia, particularly in the context of AI-generated music. The method used is normative legal research with a comparative law approach to compare international policies related to AI copyright and adapt them into Indonesia’s legal system. The results reveal that based on Law No. 28 of 2014 concerning Copyright, AI cannot be recognized as an author because it does not meet the “human” criteria required to obtain copyright protection. Furthermore, in international practice, some countries have begun to recognize AI-generated works by granting copyright to humans involved in the development or operation of AI. Therefore, Indonesia needs to consider updating its copyright law to accommodate advancements in AI technology while protecting the copyright of human creators. This study also recommends that Indonesia adopt international approaches to clarify copyright protection for AI-generated works by emphasizing human involvement in the creative process.